The effects of different acupuncture modalities on postoperative cognitive function in elderly Chinese patients undergoing general anesthesia: a network meta-analysis - Liang, Wenjie; Li, Mengzhong; Zhang, Jianguo; Liang, Wei (Frontiers in Neurology, 2025)
BackgroundPostoperative cognitive dysfunction (POCD) is a syndrome characterized by long-term cognitive impairment following anesthesia and surgery. Acupuncture has demonstrated potential therapeutic benefits in managing POCD. However, comparative efficacy among different acupuncture modalities remains unexplored. This study aims to systematically compare the effects of various acupuncture interventions on postoperative cognitive function in elderly patients undergoing general anesthesia.MethodsA comprehensive literature search was conducted across eight databases—CNKI, Wanfang, VIP, SinoMed, PubMed, Embase, Cochrane Library, and Web of Science—up to January 2025. Randomized controlled trials (RCTs) assessing acupuncture interventions for POCD in elderly patients receiving general anesthesia were included, provided cognitive outcomes were measured by the Mini-Mental State Examination (MMSE) or reported POCD incidence. Study quality was appraised using the Cochrane Risk of Bias Tool 2.0. A Bayesian network meta-analysis (NMA) was performed with the GEMTC package in R software, incorporating both direct and indirect comparisons. Intervention rankings were evaluated using the Surface Under the Cumulative Ranking Curve (SUCRA). Statistical significance was set at p < 0.05. Publication bias was assessed by funnel plots generated in Stata 18.0.ResultsThirty-two studies involving 2,644 patients were included. The SUCRA rankings for efficacy in improving postoperative cognitive function were: Electroacupuncture (77.93%) > Thumbtack Needle (73.89%) > Scalp Acupuncture (68.58%). Subgroup analysis by intervention timing revealed: preoperative phase—electroacupuncture was significantly superior to conventional anesthesia and thumbtack needle; intraoperative phase—electroacupuncture outperformed scalp acupuncture and placebo; postoperative phase—electroacupuncture showed the best efficacy, surpassing conventional anesthesia and Xingnao Kaiqiao acupuncture; perioperative phase—auricular acupuncture exhibited notable advantages over electroacupuncture and standard of care. Regarding POCD incidence, 23 studies with 1,886 patients demonstrated SUCRA rankings as: Xingnao Kaiqiao acupuncture (86.56%) > Thumbtack Needle (80.16%) > Electroacupuncture (58.78%).ConclusionElectroacupuncture exerted the most substantial effect in mitigating postoperative declines in Mini-Mental State Examination (MMSE) scores among elderly Chinese patients receiving general anesthesia. Thumbtack needle acupuncture and scalp acupuncture also showed relatively favorable benefits. Electroacupuncture consistently achieved superior outcomes across preoperative, intraoperative, and postoperative interventions.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251061472.